The link between innovation organization culture and leadership in Lithuanian companies - Sukackaitė, Rugilė; Atkočiūnienė, Zenona Ona (Information & Media, 2016)
Constant competition in nowadays hyperdynamic environment is one of the key conditions that encourage the organizations to look for the best ways to increase their performance. New, creative and productive ideas, permanent development of the employees’ competences provide the basis for the successful development and competitive advantage of the organization. Innovation potential is highly influenced by the organizational culture. Scientists agree that in order to create and develop innovations, it is important to form innovation culture with its elements: positive emotional environment, knowledge management, creativity and change management. For the continuous development of innovation culture it is important to have a leader who could promote innovation processes by forming the environment based on trust and openness.The aim of the article is to define the innovation culture construct and analyze its relationship with the leadership. To achieve this goal, empirical study was carried out by using survey method and the following things were measured: the level of innovation culture and leadership existence; the links among innovation culture elements; the link between innovation culture and leadership; the link between innovation culture and innovation performance in Lithuanian companies. The research revealed that innovation culture elements are connected to each other. Additionally, the research confirmed the relationship between innovation culture and transformational leadership and revealed that innovation culture has a positive and strong influence on innovation performance.
Keywords: ...